Аналитическое определение шероховатости поверхности при абразивной обработке отверстий - Новиков, Федор Васильевич; Минчев, Роман Михайлович (НТУ "ХПИ", 2015)
Произведен расчет шероховатости поверхности при абразивной обработке на основе использования теории вероятностей и выполнен анализ закономерностей изменения шероховатости поверхности при шлифовании отверстия. Установлено, что шероховатость поверхности однозначно определяется суммарным количеством зерен, участвующих в формировании шероховатости. Обоснованы преимущества хонингования по сравнению с внутренним шлифованием. Показана возможность уменьшения шероховатости поверхности при шлифовании кругом, ось которого расположена перпендикулярно оси вращения обрабатываемой детали.

The roughness of the surface during abrasive processing is calculated using probability theory. The patterns of changes in the surface roughness when grinding a hole are analyzed analytically. It is proved that the surface roughness is determined completely and unambiguously by the total amount of abrasive grains participating in the formation of the surface roughness of the treated surface. The advantages of honing compared to internal grinding are justified. The possibility of substantial reduction of surface roughness by using a grinding circle with the axis perpendicular to the axis of rotation of the workpiece is shown. The greatest effect is achieved when processing by the end face of a grinding wheel having circular shape and providing maximum contact area with the inner surfaces of the machined parts. To realize the proposed scheme of the internal grinding of an opening the abrasive grains must be located approximately at the same height on the working surface of the wheel. Otherwise, cutting will involve only the most protruding grains which will lead to the formation of individual scratches on the treated surface and will not let to reduce substantially the surface roughness.
Analytical determination of surface roughness in the abrasive machining of holes
Keywords: шлифование; хонингование; абразив свободный; зерно абразивное; grinding; honing; hole